Eficiencia del acetato de lecirelina para inducir la ovulación en yeguas - Merizalde Jiménez, Wendy Alejandra (2025)
Ovulation synchronization is an essential tool in equine reproduction programs, as it allows for optimizing timing for artificial insemination or natural mating. Lecirelin is a GnRH analog that was recently approved as an ovulation inducer in the equine species; however, there are few studies demonstrating the appropriate conditions for its use. The objective of this study was to evaluate the efficiency of lecirelin acetate as an ovulation inducer in mares and its influence on follicular dynamics. Nine crossbred cyclic mares, aged between 12 and 19 years, were used during three estrous cycles. These cycles were randomly distributed so that all mares underwent the following three treatments: LECIRE_100 (100 μg of lecirelin acetate), LECIRE_150 (150 μg of lecirelin acetate), and the control treatment DESLO (1.8 mg of deslorelin acetate). Mares were induced when a preovulatory follicle >35 mm in diameter and uterine edema grade 2-3 were detected. To assess ovulation rate and timing, as well as follicular growth, ultrasound monitoring was performed at 36, 42, and 48 hours post-treatment via intramuscular (IM) application. The results showed no statistically significant differences in ovulation rate (LECIRE_100 and LECIRE_150: 77.77%, DESLO: 100%), mean ovulation time (LECIRE_100: 40.71 h, LECIRE_150: 41.01 h, and DESLO: 42.40 h), or follicular growth per day (LECIRE_100: 2.02 mm, LECIRE_150: 2.28 mm, and DESLO: 1.67 mm). It is concluded that lecirelin acetate at doses of 100 and 150 μg is as effective as deslorelin acetate in inducing ovulation in mares, providing an alternative where deslorelin availability is limited.